'I think it just made everything very much more intense': a qualitative secondary analysis exploring the role of friends and family providing support to survivors of domestic abuse during the COVID-19 pandemic - Gregory, Alison (Journal of family violence, 2022)
The COVID-19 pandemic, and associated social restrictions, have amplified women’s experiences of domestic abuse (DA). In usual times, female DA survivors reach out to those around them (friends, family members, neighbors, and colleagues) for support. Accessing of both professional and informal support by survivors has increased during the pandemic. Informal supporters are often deeply invested and immersed in situations of DA because of the closeness of relationships. The accounts of informal supporters are rarely sought, yet these are people who may have a considerable awareness of what is happening. The aim of this study was to explore how the pandemic had impacted people’s assessment of abusive situations and their ability to provide informal support. This paper reports a secondary analysis of qualitative data collected in 2020 in England. The data were gathered in 18 in-depth interviews with people who knew a female friend, relative, neighbor, or colleague who had experienced DA. The age range of participants was 25–69 years, three were men and fifteen were women. A reflexive thematic analysis was carried out. Findings indicated: (i) the pandemic had changed people’s ability to read situations and assess risk (ii) perpetrators were exploiting the pandemic to further abuse (iii) within the context of the pandemic there was additional challenge to offering support (iv) informal supporters found creative ways to remain in-touch and to continue offering support. Further research with informal supporters is needed to ascertain how best to support and equip people, without imposing an impossible burden.